2010
DOI: 10.1016/j.ntt.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Excess omega-3 fatty acid consumption by mothers during pregnancy and lactation caused shorter life span and abnormal ABRs in old adult offspring

Abstract: Consuming omega-3 fatty acids (ω-3 FA) during pregnancy and lactation is beneficial to fetal and infant development and might reduce the incidence and severity of preterm births by prolonging pregnancy. Consequently, supplementing maternal diets with large amounts of ω-3 FA is gaining acceptance. However, both over-and under-supplementation with ω-3 FA can harm offspring development. Adverse fetal and neonatal conditions in general can enhance age-related neural degeneration, shorten life span and cause other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
47
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 83 publications
20
47
1
Order By: Relevance
“…We have previously found that under some conditions that high levels of DHA could be toxic (Church et al ., 2010). In order to assure that this was not the case under the conditions employed in these experiments, in figure 1 Jurkat T cells were exposed to 5 μM Hg 2+ or vehicle control .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that under some conditions that high levels of DHA could be toxic (Church et al ., 2010). In order to assure that this was not the case under the conditions employed in these experiments, in figure 1 Jurkat T cells were exposed to 5 μM Hg 2+ or vehicle control .…”
Section: Resultsmentioning
confidence: 99%
“…(36) On the other hand, the adverse effects of fish oil, including those reported in this study, have also been reported. (17,5254) Accordingly, it will be necessary to further examine the ingestion level and the duration of fish oil, and to establish methods to effectively use fish oil in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This was done at each stimulus intensity level in order to derive amplitude-intensity (A-I) profiles. Whereas the ABR amplitude is a function of neural synchrony and the number of neural units firing, the ABR amplitude can provide diagnostic information on these neural functions [26,71,89] and the presence of hyperacusis [15]. …”
Section: Methodsmentioning
confidence: 99%